DE VOLTA PARA CASA: ESTUDO COM EGRESSOS DE HOSPITAIS PSIQUIATRICOS - Ribeiro, Iana Profeta (2006)
The purpose of this research was to describe and to analyze the impact of the program De volta para casa, in the consolidation of the Psychiatric Reform in Brazil. Methodology: It is a research of qualitative character with case study. The research was developed in three therapeutic home located in the city Santo André (SP); the subjects of the investigation were the 25 in habitants of these homes. The results were analyzed, according to the theoretical basis of Bardin. Final Considerations: The therapeutic home services show their efficient importance, all involved from managers to technicians realize the objective of the consolidation of this equipment that demands a process of daily construction. It was observed that the great preoccupation of the service is with people and their group relations that enable sharing among those who present different forms of contracts and autonomy. Thus, it was possible to realize an enrichment of the social reinsertion contracts.